Strategi komunikasi pemasaran digital subway indonesia melalui reels instagram @subway.indonesia - Kiki Resky Ramdhani Sucipto; Andi Fauziah Yahya (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
The food and beverage business is one of the fastest growing industries in recent years. In this industry a lot of creativity and innovative inventions. The food and beverage industry is expected to continue to be the main driver of manufacturing expansion and the national economy. To survive in business, it is necessary to have the right business strategy, one of which is carried out by Subway Indonesia, which has re-opened outlets in Indonesia. The purpose of this research is to find out how Subway Indonesia's digital marketing communication strategy is through Instagram @subway.indonesia reels. The method used is Krippendorff content analysis which is carried out through digital observations on the @subway.indonesia Instagram account from 15 October 2021 to 31 December 2021. The results of this study indicate that Subway Indonesia is more engaged in digital marketing communication strategies through Instagram @subway.indonesia reels which are dominated by advertising strategies.